Characterization of Protostane Triterpenoids in Dried Tuber of Alisma orientalis by Q-TOF Mass Spectrometry in Both Positive and Negative Modes - Song1, Chengwu; Huang2, Long; Huang1, Xiaofei; Huang1, Rongzeng; Peng4, Min; Le5, Zhiyong; Song1, Ye; Yu1, Shanggong; Fang1, Nianbai (Asian Journal of Chemistry, 2013)
Dried tuber of Alisma orientalis (Ze Xie) is a traditional Chinese medicine. It has been characterized by high concentrations of protostane triterpenoids, which are believed to play a crucial role for its clinical curative effect. This study describes a reliable and sensitive method for the analysis of protostane triterpenoids in Dried tuber of Alisma orientalis. The protostane triterpenoids were studied by HPLC/Q-TOF-mass spectrometry. A total of 28 protostane triterpenoids were simultaneously detected in Q-TOF-MS and 15 of them were newly found in Ze Xie. Especially, we focused on the CID MS/MS fragmentation patterns of 3 major components with different MS/MS collision energy at 15 or 35 eV and obtained extensive fragmentation information in structural elucidation. This is the first report regarding to the CID MS/MS fragmentation patterns of protostane triterpenoids in Ze Xie with both positive and negative modes. The results suggest that the method could be applied to analysis of protostane triterpenoids in Ze Xie and other herbs.